Poverty and entrepreneurship in developed economies - Morris, Michael H.; Santos, Susana C.; Neumeyer, Xaver (Cheltenham, UK ; Northampton, MA : Edward Elgar Publishing, 2018)
While extensively explored as a solution to poverty at the base of the pyramid, this is the first in-depth examination of entrepreneurship and the poor within advanced economies. The authors explore the underlying nature of poverty and draw implications for new venture creation. Entrepreneurship is presented as a source of empowerment that represents an alternative pathway out of poverty.
Includes bibliographical references and index.
Keywords: Social entrepreneurship -- Developed countries; Poverty -- Developed countries -- Prevention; Poor -- Employment -- Developed countries